Analysis of nationwide hemophilia care: A cohort study using two Japanese healthcare claims databases. Issue 1 (27th January 2022) - Kinai, Ei; Ono, Midori; Oh, Akinori; Ota, Mihoko; Myaguchi, Yasuo; Ueda, Hitoshi
Abstract: Background and aims: In many developed countries, hemophilia care is provided by specialized centers which can offer standardized high‐quality care for patients and collect data for patient registries. However, in countries with less centralized provision of hemophilia care, registry data lacks accuracy and medical care is inconsistent among providers. Claims databases can be an alternative for obtaining nationwide data on hemophilia care, and we applied this approach to evaluate inequalities in hemophilia care in Japan. Methods: Medical records of hemophilia A patients were collected by a combination of ICD‐10 code (D66) and prescribed coagulation factors from two major Japanese claims databases (JMDC and Medical Data Vision [MDV]). Patient records with an anti‐inhibitor coagulant complex were excluded. Based on the annual number of hemophilia A patients, medical facilities were categorized into specialized facilities (SP, ≥5 patients) and nonspecialized facilities (N‐SP, <5 patients). Patient age, comorbidities, diagnostic testing, prescribed drugs and their dosages were compared between facility types. Results: The JMDC and MDV databases included 274 and 1266 hemophilia A patients, respectively. In the MDV database, SP facilities prescribed extended half‐life factor VIII (FVIII) products for more patients (31.8% vs 24.3%) than N‐SP. The mean annual FVIII consumption per patient was higher in SP facilities (240 333 IU [international units] vs 210 334 IU), and the mean FVIII dosage was higher in SP facilities for all types of FVIII products. The proportion of patients who received diagnostic blood tests was higher in SP (75.7% vs 56.2%). Conclusion: The MDV database revealed disparities in hemophilia A care between SP and N‐SP facilities in types of FVIII products prescribed, FVIII consumption, and frequency of the relevant management such as blood tests. Claims databases can be an alternative for the assessment of nationwide hemophilia care patterns in countries without a well‐established registry.